Large‐Area Perovskite Film Prepared by New FFASE Method for Stable Solar Modules Having High Efficiency under Both Outdoor and Indoor Light Harvesting. Issue 7 (16th January 2023) - Chiang, Chien‐Hung; Wu, Chun‐Guey
Abstract: High‐quality perovskite film is deposited on a 30 cm × 40 cm LiCoO2 ‐coated ITO/glass via newly developed freely falling anti‐solvent extraction (FFASE) method followed by post watervapor annealing in an ambient atmosphere. Perovskite solar modules (PSMs, active area of 25.2 cm 2 with mask) based on this high‐quality film achieve the highest efficiency of 16.04 and 30.76% under 1 sun (100 mW cm −2 ) and 945 lux fluorescent light illumination, respectively. The encapsulated PSMs are stable at −20 to 80 °C thermal cycling and keep high efficiency at temperature as low as −20 °C and as high as 80 °C. When the encapsulated PSM is heated at 85 °C and 85% relative humidity under room lighting or heated at 60 °C under AM1.5 (100 mW cm −2 ) illumination for 1000 h, loses only ≈8% of its original efficiency. The high stability of PSMs is due to very high quality perovskite absorber being used. The underlying concept of the FFASE method for extracting the solvent from the large‐area perovskite precursor film is that the whole precursor film contacts with the fresh anti‐solvent during the crystallization stage. Abstract : High‐quality perovskite film is deposited on a 30 cm × 40 cm LiCoO2 ‐coated ITO/glass via newly developed freely falling anti‐solvent extraction followed by post water vapor annealing in an ambient atmosphere. Perovskite solar modules based on this high‐quality film achieve the power conversion efficiency of 16.04% under 1 sun and very stable at temperature between −20 and 80 °C.